Complex Analysis of Quality Indices of Ice Cream with the Use of Milk and Protein Concentrates - Osmak (Fedchenko), Tetiana; Polishchuk, Galyna; Kochubei-Lytvynenko, Oksana; Mykhalevych, Artur (My University, 2019)
The scientific and practical interest in the dairy industry is the development aimed at obtaining food with high nutritional value, which corresponds to the basic concept of balanced and rational nutrition. These products include the technology of frozen desserts (ice cream) using milk -protein concentrates. At the Department of Technology of Milk and Dairy Products of the National University of Food Technologies (Kyiv, Ukraine), ice cream formulations were developed, which include full -fledged protein concentrates - cottage cheese and soy protein concentrate.
Keywords: ice cream; milk -protein concentrates; complex analysis; морозиво; молочно-білкові концентрати; комплексний аналіз; кафедра технології молока і молочних продуктів